Marsupials and rodents (Didelphimorphia and Rodentia) of upper Rio Acre, with new data on Oxymycterus inca Thomas, 1900 from Brazil - Edson Abreu-Júnior; Marco de Freitas; Marina Lapenta; Nathocley Venâncio; Daniella de França; Alexandre Percequillo (Check List, 2016)
Our goal was to inventory marsupial and rodent species from two conservation units (Reserva Extrativista Chico Mendes and Estação Ecológica do Rio Acre) of the upper Rio Acre, in Brazilian Amazonia, as well as to provide new data on the morphology and geographic distribution for several species. We recorded 25 species, including seven marsupials and 18 rodents. Among these, there are poorly sampled species in Brazil, such as Marmosa regina and Dactylomys boliviensis. We document range extensions (about 450 km towards southeastern Acre state) of Neacomys musseri, Dasyprocta fuliginosa, and Proechimys cuvieri. We also present the first confirmed record of an undescribed species of Monodelphis in Acre state and the second collecting record of Oxymycterus inca in Brazil. We describe the morphology and morphometrics of upper Rio Acre specimens of O. inca. Finally, we compare our results with other inventories in the Amazon region and discuss the high efficiency of pitfall traps for capturing nonvolant small mammals.